2021
DOI: 10.1039/d0nj06081j
|View full text |Cite
|
Sign up to set email alerts
|

Y–F co-doping behavior of LiFePO4/C nanocomposites for high-rate lithium-ion batteries

Abstract: Lithium iron phosphate (LFP) has become one of the current mainstream cathode materials due to its high safety and low price. Most methods (e.g. ion doping, carbon coating and particle...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Nevertheless, it seems LFP in the co-fired LFP/LATP composite cathode could be activated by charge-discharge because taking out of Li-ions allows higher transportations of both ions and electrons within LFP. [73,74] Therefore, more active sites are available for the next chargedischarge cycle until a steady state is reached. The cell with discharge cut-off voltage at 2.2 V has the same trend of increasing capacity until the 4th cycle (Figure 4e,f).…”
Section: Electrochemical Performance Of Co-fired Lfp/latp Composite C...mentioning
confidence: 99%
“…Nevertheless, it seems LFP in the co-fired LFP/LATP composite cathode could be activated by charge-discharge because taking out of Li-ions allows higher transportations of both ions and electrons within LFP. [73,74] Therefore, more active sites are available for the next chargedischarge cycle until a steady state is reached. The cell with discharge cut-off voltage at 2.2 V has the same trend of increasing capacity until the 4th cycle (Figure 4e,f).…”
Section: Electrochemical Performance Of Co-fired Lfp/latp Composite C...mentioning
confidence: 99%
“…Another idea of dual‐layer coating is that the inner layer with high ionic conductivity can tightly immobilize on the cathode surface and the outer layer function as an isolated layer from the electrolyte. [ 196,198,199 ] Li et al. [ 199 ] coated NCM with Li x Ni 1‐ y Fe y O 2 and NiFe 2 O 4 using a straightforward wet chemical method ( Figure a).…”
Section: Cathode For Lithium/sodium‐ion Batteriesmentioning
confidence: 99%
“…The high volumetric energy density of 427 W h L −1 under 60C was achieved. Wang et al 70 synthesized lithium iron phosphate (LFP) with Y–F co-doping. It was observed that the electronic conductivity increased upon doping with F owing to the rearrangement of the PO 4 3+ electron cloud.…”
Section: Electrodes For Li-ion Batteriesmentioning
confidence: 99%